2022
DOI: 10.1001/jama.2022.10777
|View full text |Cite
|
Sign up to set email alerts
|

Minor Consent Laws for Sexually Transmitted Infection and HIV Services

Abstract: This study examines current minor consent laws for sexually transmitted infection/HIV services and related confidentiality protections in all 50 states and the District of Columbia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Additionally, rural physicians may require training in how to disclose to parents/guardians that their minor tested positive for HIV, especially if they are required to by state law or decide to own their own. 32 This study found that rural respondents were overall less comfortable in all of the PrEP-related clinical activities than urban respondents. This might be unsurprising as rural SMM have indicated their local PCPs are unknowledgeable about PrEP, are reluctant to prescribe it, and are uncomfortable talking about sex.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Additionally, rural physicians may require training in how to disclose to parents/guardians that their minor tested positive for HIV, especially if they are required to by state law or decide to own their own. 32 This study found that rural respondents were overall less comfortable in all of the PrEP-related clinical activities than urban respondents. This might be unsurprising as rural SMM have indicated their local PCPs are unknowledgeable about PrEP, are reluctant to prescribe it, and are uncomfortable talking about sex.…”
Section: Discussionmentioning
confidence: 65%
“…Rural physicians need to be trained in how to disclose an HIV‐positive result to adolescent patients. Additionally, rural physicians may require training in how to disclose to parents/guardians that their minor tested positive for HIV, especially if they are required to by state law or decide to own their own 32 …”
Section: Discussionmentioning
confidence: 99%
“…42 Peer navigators can also assist young people in engaging with complex healthcare institutions, 52 with peer organizations collaborating with NGOs and CBOs to advocate shifts in institutional norms to promote youth-friendly practices, such as ensuring thorough implementation of minor consent regulations to protect adolescents' confidentiality in accessing PrEP. 53 Finally, a practice-based HIV prevention framework illustrates the counterproductive impacts of Thai government regulations announced in October 2022, which discontinue government funding to reimburse civil society groups for the costs of PrEP and HIV testing of individuals not covered by Universal Health Care. 10,54 With an estimated 60% to 70% of PrEP in Thailand provided through civil society organizations -including the preponderance of gay and transgender people who choose to avoid discrimination and stigma from HCPs in government clinics despite having Universal Health Coverage -this policy reversal in effect discontinues coverage for the majority of people currently receiving PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…In Reply State laws that enable minors to consent independently to health care have important limitations, including those raised by Mr Kels. Minor consent regimes are complex and often require simultaneous application of multiple statutes, which makes the laws difficult to interpret and trust.…”
mentioning
confidence: 95%